2015
DOI: 10.3109/13880209.2015.1028078
|View full text |Cite
|
Sign up to set email alerts
|

Compounds fromSedum caeruleumwith antioxidant, anticholinesterase, and antibacterial activities

Abstract: Context: This is the first study on the phytochemistry, antioxidant, anticholinesterase, and antibacterial activities of Sedum caeruleum L. (Crassulaceae). Objective: The objective of this study is to isolate the secondary metabolites and determine the antioxidant, anticholinesterase, and antibacterial activities of S. caeruleum. Materials and methods: Six compounds (1-6) were isolated from the extracts of S. caeruleum and elucidated using UV, 1D-, 2D-NMR, and MS techniques. Antioxidant activity was investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 29 publications
1
17
0
1
Order By: Relevance
“…(Crassulaceae) delayed the growth of bacteria. Similarly, Bensouici et al () found that the activities of Escherichia coli , Pseudomonas aeruginosa, and Staphylococcus aureus were obviously inhibited when treated with flavonoids from Sedum caeruleum L. (Crassulaceae). In our present work, the results of growth and time–kill curves showed that flavonoids from S. aizoon L. could prevent the logarithmic long‐term proliferation of Aeromonas .…”
Section: Discussionmentioning
confidence: 92%
“…(Crassulaceae) delayed the growth of bacteria. Similarly, Bensouici et al () found that the activities of Escherichia coli , Pseudomonas aeruginosa, and Staphylococcus aureus were obviously inhibited when treated with flavonoids from Sedum caeruleum L. (Crassulaceae). In our present work, the results of growth and time–kill curves showed that flavonoids from S. aizoon L. could prevent the logarithmic long‐term proliferation of Aeromonas .…”
Section: Discussionmentioning
confidence: 92%
“…Thus, further purification was focused on the two flavonoids-enriched fractions (C and D). The isolated compounds ( Fig.1) included quercetin (1) [16], isorhamnetin 3-O-b-D-glucoside (2) [17], eriodictyol (3) [18], pyracanthoside (4) [19], apigenin (5) [20], apigetrin (6) [20], acacetin (7) [21], acacipetalin (8) [21], luteolin (9) [16], diosmetin (10) [22], spinacetin (11) [16], axillarin (12) [16], bonanzin (13) [23], cirsiliol (14) [24], chrysosplenol D (15) [25] and artemetin (16) [23], and were characterized by detailed spectroscopic analysis and comparing with the previous literature data. Among them, compounds 11-16 have never been reported from Chrsanthemum species before, and 14 compounds (1-3, 5-7, 9-16) were isolated from Chuju for the first time.…”
Section: Bioassay Guided Isolation and Structural Identification Of Fmentioning
confidence: 99%
“… 2004 ; Bensouici et al. 2016 ). One millilitres of copper (II) chloride solution (0.01 M prepared from CuCl 2 ·2H 2 O), 1 mL of ammonium acetate buffer at pH 7.0 and 1 mL of neocaproin solution (0.0075 M) were mixed to 0.5 mL of plant extract or standard of different concentrations solution.…”
Section: Antioxidant Activitymentioning
confidence: 99%